Malformasi Arteriovena Pada Bekas Seksio Sesaria - Yusrawati, Yusrawati (Fakultas Kedokteran Universitas Andalas, 2017)
Uterine arteriovenous malformations is rare case which cause secondary postpartum hemorrhage. This disor-der can cause massive and suddden vaginal bleeding. Despite of rare case, secondary arteriovenous malforma-tions can occur after a cesarean section. Patients who undergo uterine arteriovenous malformation generally have symptoms of menorrhagia or metrorrhagia after miscarriage, uterine surgery, including cesarean section, and curettage. In severe cases, this can lead to malformations of dyspnoea and heart failure. Management of AVM is by embolization, methotrexate treatment and hysterectomy depending on patient condition. Here reported a case of a patient aged 25 years with a diagnosis of P2H1, AUB ec AVM. Patients got history of caesarean section 6 months ago, and since 5 months ago patients were admitted 8 times for recurrent bleed-ing. Diagnostic examinations found AVM and hysterectomy was done. The AUB diagnosis in patients is less precise, the patient should be diagnosed with secondary postpartum hemorrhage due to uterine arteriovenous malformation acquired. Uterine arteriovenous malformation diagnosis should be considered in patients with secondary postpartum haemorrhage.Keywords: arteriovenous malformation, a former cesarean section, AUB